Binder composition for secondary battery, slurry composition for secondary battery, solid electrolyte-containing layer, all-solid-state secondary battery, and method for producing all-solid-state secondary battery
Patent Information
- Application Number
- JP2021567089
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-26
- Filing Date
- 2020-11-26
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2040-11-26
AI Technical Summary
【0019】 本発明によれば、二次電池の耐水性を向上させることができると共に、二次電池に優れた電池特性を発揮させ得る二次電池用バインダー組成物を提供することができる。 また、本発明によれば、二次電池の耐水性を向上させることができると共に、二次電池に優れた電池特性を発揮させ得る二次電池用スラリー組成物を提供することができる。 さらに、本発明によれば、耐水性に優れた固体電解質含有層、並びに、電池特性に優れた全固体二次電池およびその製造方法を提供することができる。
Smart Images

Figure 0007652082000001 
Figure 0007652082000002 
Figure 0007652082000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a binder composition for a secondary battery, a slurry composition for a secondary battery, a solid electrolyte-containing layer, an all-solid-state secondary battery, and a method for producing an all-solid-state secondary battery. [Background technology]
[0002] Secondary batteries, exemplified by nonaqueous electrolyte secondary batteries (hereinafter sometimes abbreviated as "nonaqueous secondary batteries") using an organic solvent electrolyte and all-solid-state secondary batteries using a solid electrolyte instead of an organic solvent electrolyte, are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and are used for a wide range of applications.
[0003] Here, when preparing a battery component for a secondary battery, a binder composition for a secondary battery containing a polymer as a binder and an organic solvent is used. Specifically, the binder composition is mixed with, for example, a component to be blended in order to cause the battery component to exhibit a desired function, to prepare a slurry composition for a secondary battery. Next, the organic solvent is removed from the slurry composition for a secondary battery to form an electrode mixture layer, a solid electrolyte layer, or the like for a secondary battery, which can be used as a battery component or a part of a battery component.
[0004] In order to improve the performance of secondary batteries, improvements have been made to binder compositions for secondary batteries. For example, Patent Document 1 provides a binder composition for a positive electrode of a non-aqueous secondary battery, which contains a specific polymer and an organic solvent, and the solution turbidity of the binder composition for a positive electrode of a non-aqueous secondary battery is within a predetermined range. Moreover, Patent Document 2 provides a solid electrolyte composition containing a specific inorganic solid electrolyte (A), a dehydrating agent (B), and a dispersion medium (C). Patent Document 3 provides an all-solid-state secondary battery having a positive electrode active material layer, an inorganic solid electrolyte layer, and a negative electrode active material layer in this order, in which at least one of the positive electrode active material layer, the inorganic solid electrolyte layer, and the negative electrode active material layer each contains a cyclic compound having at least a siloxane bond, and an inorganic solid electrolyte that contains a metal belonging to Group 1 or 2 of the periodic table and has ion conductivity. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2018-160421 A [Patent Document 2] International Publication No. 2017 / 199821 [Patent Document 3] JP 2016-33917 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the conventional binder compositions described above have room for improvement in terms of improving the water resistance of secondary batteries and enabling the secondary batteries to exhibit excellent battery characteristics.
[0007] Therefore, an object of the present invention is to provide a binder composition for a secondary battery that can improve the water resistance of the secondary battery and enable the secondary battery to exhibit excellent battery characteristics. Another object of the present invention is to provide a slurry composition for a secondary battery that can improve the water resistance of the secondary battery and enable the secondary battery to exhibit excellent battery characteristics. Furthermore, an object of the present invention is to provide a solid electrolyte-containing layer having excellent water resistance, an all-solid-state secondary battery having excellent battery characteristics, and a method for producing the same. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to solve the above problems, and have newly discovered that the use of a binder composition containing a polymer, an organic solvent, and an inorganic or organic compound containing a specific element and having specific properties can improve the water resistance of a secondary battery and enable the secondary battery to exhibit excellent battery characteristics, thereby completing the present invention.
[0009] That is, the present invention aims to advantageously solve the above problems, and the binder composition for secondary batteries (hereinafter, also simply referred to as "binder composition") of the present invention is a binder composition for secondary batteries containing a polymer, an organic solvent, and a compound consisting of an organic or inorganic substance, the compound having a solubility of 10 mass% or less in water at a temperature of 25°C, and containing an element belonging to Group 13 and / or Group 14 of the periodic table (excluding carbon and germanium), and the content of the element in the binder composition for secondary batteries is 5 mass ppm or more and 5000 mass ppm or less with respect to the polymer. In this way, a binder composition containing a polymer, an organic solvent, and a compound having a solubility in water of a predetermined value or less and containing a predetermined element, and the content of the element in the binder composition is within a predetermined range, can improve the water resistance of a secondary battery by using such a binder composition, and can cause the secondary battery to exhibit excellent battery characteristics.
[0010] In the binder composition for secondary batteries of the present invention, the polymer preferably has at least one functional group selected from the group consisting of a carbonyl group, an ether group, a carboxy group, and a hydroxy group. By using a polymer having the specific functional group described above, the adhesiveness of the polymer can be improved.
[0011] In the binder composition for secondary batteries of the present invention, the compound preferably has at least one structure selected from the group consisting of -O-Si-O-, SiO2, and -O-Al-O-. If the compound contained in the binder composition of the present invention has at least one structure selected from the group consisting of -O-Si-O-, SiO2, and -O-Al-O-, the use of such a binder composition can further improve the water resistance of the secondary battery and can allow the secondary battery to exhibit more excellent battery characteristics.
[0012] In the binder composition for a secondary battery of the present invention, the polymer preferably contains at least one of vinyl cyanide monomer units, aromatic monomer units, or conjugated diene monomer units and / or alkylene structural units in the ratios shown in (i) to (iii) below. (i) Vinyl cyanide monomer units: 2% by mass or more and 35% by mass or less (ii) Aromatic monomer units: 5% by mass or more and 40% by mass or less (iii) Conjugated diene monomer units and / or alkylene structural units are 20% by mass or more and 60% by mass or less When the polymer contained in the binder composition contains at least any one of vinyl cyanide monomer units, aromatic monomer units, and conjugated diene monomer units and / or alkylene structural units in the above-mentioned ratios, the dispersibility of each component contained in a slurry composition prepared using such a binder composition can be improved.
[0013] In the present invention, "containing a monomer unit" means that "a structural unit (repeating unit) derived from the monomer is contained in a polymer obtained by using the monomer." In addition, in the present invention, the content ratio of the "structural unit" in the polymer is 1 It can be measured using nuclear magnetic resonance (NMR) techniques such as H-NMR.
[0014] The present invention also aims to advantageously solve the above problems, and the slurry composition for secondary batteries (hereinafter, also simply referred to as "slurry composition") of the present invention is characterized by including any one of the binder compositions for secondary batteries described above. By using a slurry composition including any one of the binder compositions described above, the water resistance of the secondary battery can be improved and the secondary battery can exhibit excellent battery characteristics.
[0015] The slurry composition for secondary batteries of the present invention preferably contains a solid electrolyte. By using a slurry composition containing a solid electrolyte, the water resistance of the all-solid-state secondary battery can be improved and the all-solid-state secondary battery can exhibit excellent battery characteristics.
[0016] The present invention also aims to advantageously solve the above problems, and the solid electrolyte-containing layer of the present invention is characterized in that it is formed using the above-mentioned slurry composition containing the solid electrolyte. If the solid electrolyte-containing layer is formed using the slurry composition of the present invention containing the solid electrolyte, it is possible to form a solid electrolyte-containing layer that is easy to increase in density.
[0017] The present invention has an object to advantageously solve the above problems, and the all-solid-state secondary battery of the present invention is characterized by comprising the above-mentioned solid electrolyte-containing layer. The all-solid-state secondary battery of the present invention comprising the solid electrolyte-containing layer is excellent in water resistance and can exhibit excellent battery characteristics.
[0018] The present invention also aims to advantageously solve the above problems, and the method for producing an all-solid-state secondary battery of the present invention is characterized by including a step of pressing the above-mentioned solid electrolyte-containing layer at a pressure of less than 300 MPa. According to the production method of the present invention, an all-solid-state secondary battery that is excellent in water resistance and can exhibit excellent battery characteristics can be produced. Effect of the Invention
[0019] According to the present invention, it is possible to provide a binder composition for a secondary battery that can improve the water resistance of the secondary battery and enable the secondary battery to exhibit excellent battery characteristics. Moreover, according to the present invention, it is possible to provide a slurry composition for a secondary battery that can improve the water resistance of the secondary battery and enable the secondary battery to exhibit excellent battery characteristics. Furthermore, according to the present invention, it is possible to provide a solid electrolyte-containing layer having excellent water resistance, and an all-solid-state secondary battery having excellent battery characteristics, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, an embodiment of the present invention will be described in detail. The binder composition for secondary batteries and the slurry composition for secondary batteries of the present invention are used in the manufacture of secondary batteries such as non-aqueous secondary batteries and all-solid-state secondary batteries. The binder composition for secondary batteries of the present invention is used in the preparation of the slurry composition for secondary batteries of the present invention. The slurry composition for secondary batteries of the present invention is used in the formation of a solid electrolyte-containing layer such as an electrode mixture layer or a solid electrolyte layer used in an all-solid-state secondary battery. The solid electrolyte-containing layer of the present invention is formed using the slurry composition for secondary batteries of the present invention. The all-solid-state secondary battery of the present invention includes the solid electrolyte-containing layer of the present invention. The all-solid-state secondary battery of the present invention can be manufactured by the manufacturing method for an all-solid-state secondary battery of the present invention.
[0021] (Binder composition for secondary batteries) The binder composition of the present invention includes a polymer, an organic solvent, and a compound made of an organic or inorganic substance, and may further include other components as desired. Here, the binder composition of the present invention is characterized in that the compound has a solubility of 10% by mass or less in water at a temperature of 25° C. and includes an element belonging to Group 13 and / or Group 14 of the periodic table (excluding carbon and germanium), and the content of the element in the binder composition is 5 ppm by mass or more and 5000 ppm by mass or less relative to the polymer.
[0022] <Polymer> As the polymer contained in the binder composition of the present invention, any polymer that is usually used as a binder in secondary batteries can be used. Among them, it is preferable to use a polymer having at least one functional group selected from the group consisting of a carbonyl group, an ether group, a carboxy group, and a hydroxy group. If a polymer having any of the above-mentioned functional groups is used, the binding property of the polymer can be improved.
[0023] The polymer having the above-mentioned functional group can be obtained, for example, by introducing the above-mentioned functional group into a polymer. Here, the method for introducing the above-mentioned functional group into a polymer is not particularly limited, and for example, a polymer may be prepared using a monomer containing the above-mentioned functional group, or a polymer having the above-mentioned functional group at its terminal may be obtained by terminal-modifying an arbitrary polymer.
[0024] [Polymers containing carbonyl groups] The polymer having a carbonyl group is obtained by polymerizing a monomer composition containing a carbonyl group-containing monomer. Here, the carbonyl group-containing monomer may be a (meth)acrylic acid ester monomer. In this specification, (meth)acrylic means acrylic and / or methacrylic.
[0025] Examples of the (meth)acrylic acid ester monomer include alkyl acrylates such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, t-butyl acrylate, isobutyl acrylate, n-pentyl acrylate, isopentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, and stearyl acrylate; Methacrylate alkyl esters such as ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, t-butyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, isopentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, lauryl methacrylate, n-tetradecyl methacrylate, and stearyl methacrylate; and the like.
[0026] Other examples of the carbonyl group-containing monomer include polyvalent carboxylic acid esters such as methylallyl maleate, diphenyl maleate, nonyl maleate, decyl maleate, dodecyl maleate, octadecyl maleate, fluoroalkyl maleate, monoethyl maleate, diethyl maleate, monobutyl maleate, dibutyl maleate, monoethyl fumarate, diethyl fumarate, monobutyl fumarate, dibutyl fumarate, monocyclohexyl fumarate, dicyclohexyl fumarate, monoethyl itaconate, diethyl itaconate, monobutyl itaconate, and dibutyl itaconate. These may be used alone or in combination of two or more.
[0027] The content ratio of the carbonyl group-containing monomer unit derived from the carbonyl group-containing monomer in the polymer is preferably 25% by mass or more, more preferably 30% by mass or more, and even more preferably 35% by mass or more, and preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 85% by mass or less, when the total repeating units (the sum of the monomer units and the structural units) in the polymer is taken as 100% by mass. By making the content ratio of the carbonyl group-containing monomer unit in the polymer 25% by mass or more, the adhesive strength between the electrode mixture layer and the current collector can be increased by the slurry composition prepared using the binder composition of the present invention. In addition, by making the content ratio of the carbonyl group-containing monomer unit in the polymer 95% by mass or less, the dispersibility of the electrode active material and the conductive assistant can be improved in the slurry composition prepared using the binder composition of the present invention.
[0028] [Polymers containing ether groups] The polymer having an ether group is obtained by polymerizing a monomer composition containing an ether group-containing monomer, such as phenoxyethyl acrylate, ethoxylated o-phenylphenol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, allyl glycidyl ether, glycerin monoallyl ether, 4-hydroxybutyl acrylate glycidyl ether, and methoxypolyethylene glycol (meth)acrylate.
[0029] In the polymer, the content of the ether group-containing monomer unit derived from the ether group-containing monomer is preferably 5% by mass or more, more preferably 7.5% by mass or more, even more preferably 10% by mass or more, preferably 50% by mass or less, and more preferably 40% by mass or less, when the total repeating units in the polymer are taken as 100% by mass. By making the content of the ether group-containing monomer unit in the polymer 5% by mass or more, the adhesion strength between the electrode mixture layer and the current collector can be increased. In addition, by making the content of the ether group-containing monomer unit in the polymer 50% by mass or less, the dispersibility of the electrode active material and the conductive assistant can be increased in the slurry composition prepared using the binder composition of the present invention.
[0030] [Polymers containing carboxy groups] The polymer having a carboxy group is obtained by polymerizing a monomer composition containing a carboxy group-containing monomer. Here, examples of the carboxy group-containing monomer include carboxylic acid monomers such as acrylic acid, methacrylic acid, ethacrylic acid (2-ethylacrylic acid), itaconic acid, maleic acid, fumaric acid, and citraconic acid; and butenedioic acid monoalkyl ester monomers such as monomethyl maleate, monoethyl maleate, mono-n-butyl maleate, monomethyl fumarate, monoethyl fumarate, and mono-n-butyl fumarate; and other ethylenically unsaturated carboxylic acid compounds. These may be used alone or in combination of two or more.
[0031] In the polymer, the content of the carboxyl group-containing monomer unit derived from the carboxyl group monomer is preferably 1% by mass or more, more preferably 1.5% by mass or more, even more preferably 2% by mass or more, preferably 10% by mass or less, and more preferably 8% by mass or less, when the total repeating units in the polymer are taken as 100% by mass. By making the content of the carboxyl group-containing monomer unit in the polymer 1% by mass or more, the adhesion strength between the electrode mixture layer and the current collector can be increased. In addition, by making the content of the carboxyl group-containing monomer unit in the polymer 10% by mass or less, a solid electrolyte-containing layer that can exhibit excellent ion conductivity can be formed by the slurry composition prepared using the binder composition of the present invention.
[0032] [Polymers containing hydroxy groups] The polymer having a hydroxy group can be obtained by polymerizing a monomer composition containing a hydroxy group-containing monomer, such as 2-hydroxyethyl acrylate or hydroxyethylacrylamide.
[0033] In the polymer, the content of the hydroxyl group-containing monomer unit derived from the hydroxyl group-containing monomer is preferably 1% by mass or more, more preferably 1.5% by mass or more, even more preferably 2% by mass or more, preferably 10% by mass or less, and more preferably 8% by mass or less, when the total repeating units in the polymer are taken as 100% by mass. By making the content of the hydroxyl group-containing monomer unit in the polymer 1% by mass or more, the adhesion strength between the electrode mixture layer and the current collector can be increased. In addition, by making the content of the hydroxyl group-containing monomer unit in the polymer 10% by mass or less, a solid electrolyte-containing layer that can exhibit excellent ion conductivity can be formed by the slurry composition prepared using the binder composition of the present invention.
[0034] The polymer contained in the binder composition of the present invention may also contain monomer units such as, for example, vinyl cyanide monomer units, aromatic monomer units, conjugated diene monomer units and / or alkylene structural units.
[0035] [Vinyl cyanide monomer unit] Examples of vinyl cyanide monomers capable of forming vinyl cyanide monomer units include acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, and α-ethylacrylonitrile. These may be used alone or in combination of two or more. Among these, acrylonitrile is preferred.
[0036] The content of the vinyl cyanide monomer unit in the polymer is preferably 2% by mass or more, more preferably 3% by mass or more, even more preferably 4% by mass or more, and preferably 35% by mass or less, more preferably 28% by mass or less, and even more preferably 26% by mass or less, when the total repeating units in the polymer are taken as 100% by mass. By making the content of the vinyl cyanide monomer unit in the polymer 2% by mass or more, a solid electrolyte-containing layer in which the solid electrolyte is well dispersed can be formed by the slurry composition prepared using the binder composition of the present invention. In addition, by making the content of the vinyl cyanide monomer unit in the polymer 35% by mass or less, the solubility of the polymer in an organic solvent can be improved. Therefore, the slurry composition prepared using such a binder composition can improve the dispersibility of each component contained in the slurry composition.
[0037] [Aromatic monomer unit] Examples of aromatic monomers that can form aromatic monomer units include styrene, styrenesulfonic acid and its salts, α-methylstyrene, pt-butylstyrene, butoxystyrene, vinyltoluene, chlorostyrene, vinylnaphthalene, and phenoxyethyl acrylate. These may be used alone or in combination of two or more. Among these, styrene is preferred.
[0038] The content of the aromatic monomer unit in the polymer is preferably 5% by mass or more, more preferably 7% by mass or more, even more preferably 10% by mass or more, and preferably 40% by mass or less, more preferably 35% by mass or less, and even more preferably 30% by mass or less, when the total repeating units in the polymer are taken as 100% by mass. By making the content of the aromatic monomer unit in the polymer 5% by mass or more, the dispersibility of the electrode active material and the conductive assistant can be increased by the slurry composition prepared using the binder composition of the present invention. In addition, by making the content of the aromatic monomer unit in the polymer 40% by mass or less, the adhesive strength between the electrode mixture layer and the current collector can be increased by the slurry composition prepared using the binder composition of the present invention. In addition, by using the slurry composition, a solid electrolyte-containing layer in which the solid electrolyte is well dispersed can be formed.
[0039] [Conjugated diene monomer unit] Examples of conjugated diene monomers capable of forming conjugated diene monomer units include aliphatic conjugated diene monomers such as 1,3-butadiene, 2-methyl-1,3-butadiene (hereinafter referred to as "isoprene"), 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, substituted linear conjugated pentadiene, and substituted and side chain conjugated hexadienes. These may be used alone or in combination of two or more.
[0040] In the present invention, the "diene monomer unit" also includes a structural unit (hydride unit) obtained by further hydrogenating a monomer unit contained in a polymer obtained by using a diene monomer.
[0041] [Alkylene structural unit] The alkylene structural unit has the general formula: -C n H 2n It is a repeating unit composed only of an alkylene structure represented by - (where n is an integer of 2 or more).
[0042] The alkylene structural unit may be linear or branched, but is preferably linear, i.e., a linear alkylene structural unit. The alkylene structural unit preferably has 4 or more carbon atoms (i.e., n in the above general formula is an integer of 4 or more).
[0043] The method for introducing an alkylene structural unit into a polymer is not particularly limited, but may be, for example, the following method (1) or (2): (1) A method in which a polymer is prepared from a monomer composition containing a conjugated diene monomer, and the polymer is hydrogenated to convert the conjugated diene monomer unit into an alkylene structural unit. (2) A method for preparing a polymer from a monomer composition containing a 1-olefin monomer Examples include: Among these, method (1) is preferred since the polymer can be easily produced.
[0044] That is, the alkylene structural unit is preferably a structural unit obtained by hydrogenating a conjugated diene monomer unit (conjugated diene hydride unit), and more preferably a structural unit obtained by hydrogenating a 1,3-butadiene unit (1,3-butadiene hydride unit).
[0045] Examples of the 1-olefin monomer include ethylene, propylene, 1-butene, 1-hexene, etc. These may be used alone or in combination of two or more.
[0046] The content ratio of the conjugated diene monomer unit and / or the alkylene structural unit in the polymer is preferably 20% by mass or more, more preferably 25% by mass or more, even more preferably 30% by mass or more, preferably 60% by mass or less, more preferably 55% by mass or less, and even more preferably 50% by mass or less, when the total repeating units in the polymer are taken as 100% by mass. In the present invention, when both the conjugated diene monomer unit and the alkylene structural unit are contained in the polymer, it is preferable that the total of the conjugated diene monomer unit and the alkylene structural unit is within the above-mentioned range. By setting the content ratio of the conjugated diene monomer and / or the alkylene structural unit in the polymer to 20% by mass or more, the dispersibility of the electrode active material and the conductive auxiliary can be improved by the slurry composition prepared using the binder composition of the present invention. In addition, by setting the content of the conjugated diene monomer unit and / or the alkylene structural unit in the polymer to 60 mass % or less, the adhesive strength between the electrode mixture layer and the current collector can be increased by using a slurry composition prepared using the binder composition of the present invention. In addition, by using the slurry composition, a solid electrolyte-containing layer in which the solid electrolyte is well dispersed can be formed.
[0047] [Other monomer units] The polymer contained in the binder composition of the present invention may further contain other monomer units other than the above-mentioned monomers. The other monomers capable of forming such monomer units are not particularly limited, and examples thereof include crosslinkable monomers (e.g., allyl methacrylate, ethylene dimethacrylate, etc.).
[0048] <<Polymer Preparation Method>> The method for preparing the polymer contained in the binder composition of the present invention is not particularly limited. For example, the polymer can be prepared by polymerizing a monomer composition containing the above-mentioned monomers, and optionally, hydrogenating the polymer.
[0049] Here, in the present invention, the content ratio of each monomer in the monomer composition can be determined based on the content ratio of each monomer unit and structural unit in the polymer.
[0050] The polymerization method is not particularly limited, and any method such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. In each polymerization method, a known emulsifier or polymerization initiator can be used as necessary.
[0051] Furthermore, the hydrogenation method is not particularly limited, and a general method using a catalyst (for example, see WO 2012 / 165120, WO 2013 / 080989, and JP 2013-8485 A) can be used.
[0052] <Organic solvent> The organic solvent contained in the binder composition of the present invention is not particularly limited and can be appropriately selected according to the application of the binder composition.Here, examples of the organic solvent include aromatic hydrocarbons such as toluene, xylene, and mesitylene; ketones such as ethyl methyl ketone, cyclohexanone, and diisobutyl ketone; esters such as ethyl acetate, butyl acetate, butyl butyrate, hexyl butyrate, isobutyl isobutyrate, γ-butyrolactone, and ε-caprolactone; and ethers such as tetrahydrofuran, ethylene glycol diethyl ether, and n-butyl ether.These may be used alone or in combination of two or more.
[0053] For example, when a slurry composition for an all-solid-state secondary battery is prepared using the binder of the present invention, from the viewpoint of increasing the dispersibility of the solid electrolyte while suppressing deterioration due to side reactions, the organic solvent is preferably xylene, mesitylene, diisobutyl ketone, butyl butyrate, hexyl butyrate, or n-butyl ether, and more preferably xylene, mesitylene, or diisobutyl ketone.
[0054] <Compounds made of organic or inorganic substances> The organic or inorganic compound contained in the binder composition of the present invention is a compound having a solubility of 10 mass % or less in water at a temperature of 25° C. and containing an element belonging to Group 13 and / or Group 14 of the periodic table. However, in the present invention, carbon and germanium are excluded from the elements belonging to Group 13 and / or Group 14 of the periodic table.
[0055] The compound contained in the binder composition of the present invention preferably has at least one structure selected from the group consisting of -O-Si-O-, SiO2, and -O-Al-O-, and more preferably has at least one structure of -O-Si-O- and -O-Al-O-. If the compound has any of the structures -O-Si-O-, SiO2, and -O-Al-O-, a secondary battery with improved water resistance can be manufactured by using the binder composition of the present invention.
[0056] Here, examples of the compound having at least one structure selected from the group consisting of -O-Si-O-, SiO2, and -O-Al-O- include zeolite, silica gel, polydimethylsiloxane, and the like. These may be used alone or in combination of two or more. Among them, from the viewpoint of improving the water resistance and cycle characteristics of the secondary battery, zeolite, silica gel, and polydimethylsiloxane are preferred as the compound.
[0057] <Other ingredients> The other components that the binder composition of the present invention may contain are not particularly limited. Examples of the other components include binders other than the above-mentioned polymers, dispersants, leveling agents, antifoaming agents, and reinforcing materials. These other components are not particularly limited as long as they do not affect the battery reaction. In addition, these components may be used alone or in combination of two or more types in any ratio.
[0058] <Properties of the binder composition for secondary batteries> The binder composition of the present invention is a binder composition containing at least the above-mentioned polymer, an organic solvent, and a compound, and the content of the above-mentioned elements in the binder composition must be 5 ppm by mass or more and 5000 ppm by mass or less relative to the polymer. By using the binder composition of the present invention, the water resistance of the secondary battery can be improved and the secondary battery can exhibit excellent battery characteristics.
[0059] Here, the content of the above elements in the binder composition of the present invention is preferably 10 mass ppm or more, more preferably 20 mass ppm or more, even more preferably 500 mass ppm or more, preferably 4000 mass ppm or less, more preferably 3500 mass ppm or less, even more preferably 3000 mass ppm or less, and particularly preferably 2000 mass ppm or less. If the content of the above elements in the binder composition is 10 mass ppm or more with respect to the polymer, deterioration due to side reactions can be suppressed. Furthermore, if the content of the above elements is 3500 mass ppm or less with respect to the polymer, the slurry composition prepared using the binder composition of the present invention can suppress aggregation of each component in the slurry composition, thereby improving the slurry characteristics. Furthermore, if the content of the above elements is 3000 mass ppm or less with respect to the polymer, the increase in cell resistance of the secondary battery can be sufficiently suppressed.
[0060] <Method of preparing binder composition for secondary battery> The method for preparing the binder composition of the present invention is not particularly limited, and for example, the binder composition can be prepared by mixing the above-mentioned polymer, the compound, and other components used as necessary in an organic solvent. In this case, the mixing method is not particularly limited, and mixing can be performed using a commonly used stirrer or disperser.
[0061] (Slurry composition for secondary batteries) The slurry composition for secondary batteries of the present invention contains at least the binder composition for secondary batteries of the present invention described above. More specifically, the slurry composition of the present invention contains at least the above-mentioned polymer, organic solvent, and compound, and may optionally contain other components. Since the slurry composition of the present invention contains the above-mentioned binder composition, the use of such a slurry composition can improve the water resistance of the secondary battery and can cause the secondary battery to exhibit excellent battery characteristics.
[0062] Here, the slurry composition of the present invention may contain a solid electrolyte as the other component described above. According to the slurry composition containing a solid electrolyte, a solid electrolyte-containing layer having excellent water resistance can be formed by using the slurry composition.
[0063] <Method of preparing slurry composition for secondary battery> The method for preparing the slurry composition of the present invention is not particularly limited, and for example, the slurry composition can be prepared by mixing the binder composition, optionally with other components such as a solid electrolyte, using any mixing means.
[0064] <Solid electrolyte> The solid electrolyte that may be optionally contained in the slurry composition of the present invention is not particularly limited as long as it is a particle made of a solid having ion conductivity, and for example, an inorganic solid electrolyte can be used.
[0065] The inorganic solid electrolyte is not particularly limited, and a crystalline inorganic ion conductor, an amorphous inorganic ion conductor, or a mixture thereof can be used. When the solid electrolyte-containing layer formed using the slurry composition of the present invention is used in an all-solid-state lithium ion secondary battery, the inorganic solid electrolyte can usually be a crystalline inorganic lithium ion conductor, an amorphous inorganic lithium ion conductor, or a mixture thereof. In particular, from the viewpoint of forming a solid electrolyte-containing layer having even better ion conductivity, it is preferable that the inorganic solid electrolyte contains at least one of a sulfide-based inorganic solid electrolyte and an oxide-based inorganic solid electrolyte.
[0066] As crystalline inorganic lithium ion conductors, Li3N, LISICON (Li 14 Zn(GeO4)4), perovskite type (e.g. Li 0.5 La 0.5 TiO3), garnet type (e.g. Li7La3Zr2O 12 ), LIPON (Li 3+y PO 4-x N x ), Thio-LISICON (Li 3.25 Ge 0.25 P 0.75 S4) etc.
[0067] The amorphous inorganic lithium ion conductor is not particularly limited as long as it contains S (sulfur atom) and has ion conductivity (sulfide solid electrolyte material). Here, when the slurry composition of the present invention is used for a solid lithium secondary battery, the sulfide solid electrolyte material may be one made by using a raw material composition containing Li2S and a sulfide of an element of Groups 13 to 15. As a method for synthesizing a sulfide solid electrolyte material using such a raw material composition, for example, an amorphization method may be mentioned. As the amorphization method, for example, a mechanical milling method and a melt quenching method may be mentioned, and among them, the mechanical milling method is preferable. This is because the mechanical milling method enables processing at room temperature, and the manufacturing process can be simplified.
[0068] Examples of the elements of Groups 13 to 15 include Al, Si, Ge, P, As, and Sb. Examples of sulfides of elements of Groups 13 to 15 include Al2S3, SiS2, GeS2, P2S3, P2S5, As2S3, and Sb2S3. Among them, sulfides of Groups 14 or 15 are preferably used. In particular, the sulfide solid electrolyte material made by using a raw material composition containing Li2S and sulfides of elements of Groups 13 to 15 is preferably a Li2S-P2S5 material, a Li2S-SiS2 material, a Li2S-GeS2 material, or a Li2S-Al2S3 material, and more preferably a Li2S-P2S5 material. This is because these have excellent Li-ion conductivity.
[0069] The above-mentioned crystalline inorganic lithium ion conductors may be used alone or in combination of two or more. The particle size of the solid electrolyte is not particularly limited and may be the same as that of the solid electrolytes conventionally used.
[0070] (Solid electrolyte containing layer) The solid electrolyte-containing layer of the present invention (hereinafter, also simply referred to as "solid electrolyte-containing layer") is a layer formed using the slurry composition of the present invention. The slurry composition used when forming the solid electrolyte-containing layer of the present invention contains at least a solid electrolyte. Here, the solid electrolyte-containing layer of the present invention is not particularly limited, and can be used, for example, as an electrode mixture layer (positive electrode mixture layer, negative electrode mixture layer) that transfers electrons via an electrochemical reaction, or as a solid electrolyte layer provided between a positive electrode mixture layer and a negative electrode mixture layer that face each other.
[0071] The method for forming the solid electrolyte-containing layer of the present invention is not particularly limited, and can be formed, for example, by applying the above-mentioned slurry composition of the present invention containing the solid electrolyte to the surface of a suitable substrate to form a coating film, and then drying the formed coating film. That is, the solid electrolyte-containing layer of the present invention is made of a dried product of the above-mentioned slurry composition of the present invention containing the solid electrolyte, and usually contains at least a solid electrolyte, a polymer, and a compound containing an element belonging to Group 13 and / or Group 14 of the periodic table. Note that each component contained in the solid electrolyte-containing layer is contained in the above-mentioned slurry composition, and the content ratio of those components is usually equal to the content ratio in the above-mentioned slurry composition.
[0072] The content of the solid electrolyte in the solid electrolyte-containing layer can be, for example, 10% by mass or more and 100% by mass or less, and the thickness of the solid electrolyte-containing layer can be, for example, 1 μm or more and 500 μm or less.
[0073] The solid electrolyte-containing layer of the present invention is excellent in water resistance because it is formed from the slurry composition of the present invention. In addition, when the solid electrolyte-containing layer of the present invention is used as the electrode mixture layer, the electrode mixture layer can be sufficiently densified even when pressed at a pressure (pressing pressure) of less than 300 MPa.
[0074] (All-solid-state secondary battery) The all-solid-state secondary battery of the present invention includes the above-mentioned solid electrolyte-containing layer of the present invention. Here, the all-solid-state secondary battery of the present invention has, for example, a positive electrode, a solid electrolyte layer, and a negative electrode, and at least one of the positive electrode mixture layer of the positive electrode, the negative electrode mixture layer of the negative electrode, and the solid electrolyte layer is the solid electrolyte-containing layer of the present invention. The all-solid-state secondary battery of the present invention is provided with the solid electrolyte-containing layer of the present invention, and therefore has excellent water resistance and excellent battery characteristics.
[0075] Here, the all-solid-state secondary battery electrode having an electrode mixture layer that does not correspond to the solid electrolyte-containing layer of the present invention and that can be used in the all-solid-state secondary battery of the present invention is not particularly limited as long as it has an electrode mixture layer that does not correspond to the solid electrolyte-containing layer of the present invention, and any all-solid-state secondary battery electrode can be used.
[0076] In addition, the solid electrolyte layer that does not correspond to the solid electrolyte-containing layer of the present invention and that can be used in the all-solid-state secondary battery of the present invention is not particularly limited, and any solid electrolyte layer such as the solid electrolyte layers described in, for example, JP-A-2012-243476, JP-A-2013-143299, and JP-A-2016-143614 can be used.
[0077] The all-solid-state secondary battery of the present invention can be obtained by laminating a positive electrode and a negative electrode so that the positive electrode composite layer of the positive electrode and the negative electrode composite layer of the negative electrode face each other through a solid electrolyte layer, optionally applying pressure to obtain a laminate, and then placing the laminate in a battery container as is or after rolling or folding, depending on the shape of the battery, and sealing the battery. If necessary, an expand metal, a fuse, an overcurrent prevention element such as a PTC element, a lead plate, etc. can be placed in the battery container to prevent pressure rise inside the battery and overcharging and discharging. The shape of the battery may be any of a coin type, a button type, a sheet type, a cylindrical type, a square type, a flat type, etc.
[0078] (Manufacturing method of all-solid-state secondary battery) The method for producing the all-solid-state secondary battery of the present invention includes a step of pressing the above-mentioned solid electrolyte-containing layer of the present invention at a pressure of less than 300 MPa (pressing step), and may optionally include a step of applying the slurry composition of the present invention onto a substrate (application step) before the pressing step, and a step of drying the slurry composition applied onto the substrate to form a solid electrolyte-containing layer (solid electrolyte-containing layer forming step). Note that, below, a method for producing an all-solid-state secondary battery in which the solid electrolyte-containing layer of the present invention is used as an electrode mixture layer of a secondary battery will be described, but the method for producing an all-solid-state secondary battery of the present invention is not particularly limited as long as it includes at least the above-mentioned pressing step.
[0079] <Coating process> In the coating step, the slurry composition is coated on a substrate. The method for coating the slurry composition on a substrate is not particularly limited, and examples thereof include a doctor blade method, a reverse roll method, a direct roll method, a gravure method, an extrusion method, and a brush coating method.
[0080] <Solid electrolyte-containing layer formation process> In the solid electrolyte-containing layer forming step, the slurry composition on the substrate is dried. Here, the method for drying the slurry composition on the substrate is not particularly limited, and any known method can be used. Examples of the drying method include a drying method using warm air, hot air, or low-humidity air, a vacuum drying method, and a drying method using infrared rays or electron beams.
[0081] <Pressing process> In the pressing step, the solid electrolyte-containing layer is pressed at a pressure of less than 300 MPa. The method of pressing is not particularly limited, and pressing can be performed using a roll press or the like. In the method for producing an all-solid-state secondary battery of the present invention, when a solid electrolyte layer that functions as an electrode mixture layer is formed, the electrode mixture layer can be sufficiently densified even when the solid electrolyte-containing layer is pressed at a low pressure of less than 300 MPa. EXAMPLES
[0082] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. In the following description, "%" and "parts" expressing amounts are based on mass unless otherwise specified. In addition, in a polymer produced by copolymerizing multiple types of monomers, the ratio of monomer units formed by polymerizing a certain monomer in the polymer usually coincides with the ratio (feed ratio) of that certain monomer to all monomers used in the polymerization of the polymer, unless otherwise specified. In the examples and comparative examples, the content of elements belonging to Group 13 and / or Group 14 of the periodic table in the polymer in the binder composition, dispersibility, ion conductivity, peel strength of the positive electrode, cell resistance, pressing property, and cell characteristics (cycle characteristics) were measured or evaluated by the following methods. The solubility in water of the compounds used in the examples and comparative examples was measured by the following method.
[0083] <Content of elements belonging to Groups 13 and / or 14 of the Periodic Table> About 1 g of the binder composition was heated in an electric furnace at a temperature of 550° C. for about 3 hours and incinerated. Then, about 5 mL of concentrated sulfuric acid was added to the incinerated binder composition to dissolve it, and about 5 mL of concentrated nitric acid was gradually added to perform wet decomposition. After decomposition, the acid was concentrated and the volume was adjusted to 10 mL with ultrapure water, and the metal ion concentration in the binder composition was measured using an ICP-AES device (manufactured by SII Nano Technology Co., Ltd., model number "SPS-5100"). Based on the obtained metal ion concentration value, the content of elements belonging to Group 13 and / or Group 14 of the periodic table (excluding carbon and germanium) relative to the polymer contained in the binder composition was calculated.
[0084] <Dispersibility> The viscosity of the slurry composition for the solid electrolyte layer was measured with a Brookfield B-type viscometer at 60 rpm (temperature 25° C.) and evaluated according to the following criteria: The lower the viscosity of the slurry composition for the solid electrolyte layer, the better the dispersion of the solid electrolyte contained in the slurry composition for the solid electrolyte layer. A: Viscosity is less than 3000 mPa s B: Viscosity is 3000 mPa·s or more and less than 5000 mPa·s C: Viscosity is 5000 mPa·s or more but less than 8000 mPa·s D: Viscosity is 8000 mPa·s or more or does not disperse (no fluidity)
[0085] <Ionic conductivity> The slurry composition for the solid electrolyte layer was dried on a hot plate at 130°C in a glove box (water content 1 ppm or less), and the obtained powder was formed into a cylindrical shape with a diameter of 10 mm and a thickness of 1 mm to prepare a measurement sample. The lithium ion conductivity (temperature 25°C) of this measurement sample was measured by an AC impedance method. The measurement was performed using a frequency response analyzer (manufactured by Solartron Analytical, product name "Solatron (registered trademark) 1260" under the measurement conditions of an applied voltage of 10 mV and a measurement frequency range of 0.01 MHz to 1 MHz. The obtained lithium ion conductivity was designated as S0. Separately, in a dry room (water content 127 ppm or less, equivalent to a dew point of -40°C), the slurry composition for the solid electrolyte layer was dried on a hot plate at a temperature of 130°C, and the obtained powder was molded into a cylindrical shape with a diameter of 10 mm and a thickness of 0.5 mm to prepare a measurement sample. The lithium ion conductivity (temperature 25°C) of this measurement sample was measured in the same manner as S0 above. The obtained lithium ion conductivity was designated as S1. The conductivity retention rate = S1 / S0 x 100 (%) was then calculated and evaluated according to the following criteria. The higher the conductivity retention rate, the more the solid electrolyte is inhibited from deteriorating due to moisture, and the better the water resistance. In addition, the higher the conductivity retention rate, the more excellent the ion conductivity of the solid electrolyte layer (solid electrolyte-containing layer) formed using the slurry composition for solid electrolyte layer. A: Conductivity retention rate is 95% or more B: Conductivity retention rate is 85% or more and less than 95% C: Conductivity retention rate is 60% or more and less than 85% D: Conductivity retention rate is less than 60%
[0086] <Positive electrode peel strength> The positive electrode was cut into a rectangle measuring 1.0 cm wide x 10 cm long to prepare a test specimen. Cellophane tape (specified in JIS Z1522) was attached to the surface of the positive electrode composite layer of this test specimen, and the stress was measured when the cellophane tape was peeled off from one end of the test specimen in a 180° direction at a speed of 50 mm / min. The measurement was performed three times in total, and the average value was calculated and used as the peel strength (N / m) of the positive electrode, which was evaluated according to the following criteria. The higher the peel strength of the positive electrode, the better the adhesiveness of the positive electrode composite layer and the stronger the adhesion to the current collector. A+: Peel strength is 4N / m or more A: Peel strength is between 3N / m and 4N / m B: Peel strength is 2N / m or more and less than 3N / m C: Peel strength is 1N / m or more but less than 2N / m D: Peel strength is less than 1N / m
[0087] <Cell resistance> A 3-cell all-solid-state secondary battery was charged to 4.2 V by a constant current method of 0.1 C, and then discharged to 3.0 V at 0.1 C to determine the 0.1 C discharge capacity. Next, the battery was charged to 4.2 V at 0.1 C, and then discharged to 3.0 V at 2 C to determine the 2 C discharge capacity. The average value of the 0.1 C discharge capacity of the 3 cells was taken as discharge capacity a, and the average value of the 2 C discharge capacity of the 3 cells was taken as discharge capacity b. The ratio of discharge capacity b to discharge capacity a (capacity ratio) = discharge capacity b / discharge capacity a × 100 (%) was calculated and evaluated according to the following criteria. A higher capacity ratio means a lower cell resistance. A: Capacity ratio is 90% or more B: Capacity ratio is 80% or more but less than 90% C: Capacity ratio is 60% or more and less than 80% D: Capacity ratio is less than 60%
[0088] <Pressability> The prepared positive electrode was punched out to a diameter of 10 mm and pressed for 2 minutes at a specified pressure using a uniaxial press to achieve a target density of 3.3 g / cm. 3 The pressing pressure (MPa) at which the pressure reached the limit was measured and evaluated according to the following criteria. A lower pressing pressure indicates better pressing properties. A: Less than 200MPa B: 200MPa or more and less than 300MPa C: 300MPa or more and less than 400MPa D:400MPa or more
[0089] <Cell characteristics (cycle characteristics)> The obtained all-solid-state secondary battery was charged at 45°C at 0.1C from 3V to 4.2V, and then discharged at 0.1C from 4.2V to 3V, and this charge-discharge cycle was repeated 50 times. The ratio of the 0.1C discharge capacity at the 50th cycle to the 0.1C discharge capacity at the 1st cycle was calculated as a percentage, which was taken as the capacity retention rate and evaluated according to the following criteria. A higher capacity retention rate indicates less discharge capacity loss and better cell characteristics (cycle characteristics). A: Capacity retention rate is 90% or more B: Capacity retention rate is 80% or more but less than 90% C: Capacity retention rate is 70% or more but less than 80% D: Capacity retention rate is less than 70%
[0090] <Solubility of compounds in water> The solubility in water at a temperature of 25° C. of the compounds used in the examples and comparative examples was measured by the EPA method (EPA Chemical Fate testing Guideline CG-1500 Water Solubility).
[0091] Example 1 <Preparation of Binder Composition> Into a 1 L flask equipped with a stirrer and a septum, 100 parts of ion-exchanged water and 0.2 parts of sodium dodecylbenzenesulfonate as an emulsifier were added, the gas phase was replaced with nitrogen gas, and the temperature was raised to 60°C. After that, 0.25 parts of ammonium persulfate (APS) as a polymerization initiator was dissolved in 20.0 parts of ion-exchanged water and added. Meanwhile, in a separate vessel, 40 parts of ion-exchanged water, 1.0 part of sodium lauryl sulfate as an emulsifier, 69 parts of n-butyl acrylate as a carbonyl group-containing monomer, 6 parts of acrylonitrile as a vinyl cyanide monomer, and 25 parts of styrene as an aromatic monomer were mixed to obtain a monomer composition. This monomer composition was continuously added to the 1 L flask with a septum over a period of 3 hours to carry out polymerization. During the addition, the reaction was carried out at a temperature of 60°C. After the addition was completed, the mixture was stirred at a temperature of 80°C for another 3 hours to complete the reaction. Next, an appropriate amount of diisobutyl ketone was added as an organic solvent to obtain a mixture, which was then distilled under reduced pressure at a temperature of 80° C. to remove water and excess diisobutyl ketone from the mixture, obtaining a binder precursor composition (solid content: 8%). Furthermore, 5 parts of a first synthetic zeolite (manufactured by Shin-Etsu Chemical Industry Co., Ltd., product name "Molecular Sieves 4A", shape: powder, particle size: 325 mesh, solubility in water at 25°C: less than 0.1%) was added as a compound containing an element belonging to Group 13 and / or Group 14 of the periodic table to the obtained binder precursor composition, and after 24 hours, the mixture was filtered through a 10 μm filter to obtain a binder composition.
[0092] <Preparation of Slurry Composition for Positive Electrode Mixture Layer> 70 parts of lithium cobalt oxide (number average particle diameter: 11.5 μm) as a positive electrode active material, 25.5 parts of sulfide glass (Li2S / P2S5=70mol% / 30mol%, number average particle diameter: 0.9 μm) consisting of Li2S and P2S5 as a solid electrolyte, 2.5 parts of acetylene black as a conductive material, and 2 parts of the binder composition obtained as described above (solid content equivalent) were mixed, and diisobutyl ketone was further added as an organic solvent to adjust the solid content concentration to 80%, and then mixed with a planetary mixer for 60 minutes. Then, diisobutyl ketone was further added to adjust the solid content concentration to 70%, and then mixed for 10 minutes to prepare a slurry composition for the positive electrode composite layer.
[0093] <Preparation of Slurry Composition for Negative Electrode Mixture Layer> 60 parts of graphite (number average particle diameter: 20 μm) as negative electrode active material particles, 36.5 parts of sulfide glass (Li2S / P2S5=70mol% / 30mol%, number average particle diameter: 0.9 μm) consisting of Li2S and P2S5 as solid electrolyte particles, 1.5 parts of acetylene black as conductive material particles, and 2 parts (solid content equivalent) of the binder composition obtained as described above were mixed, and diisobutyl ketone was further added as an organic solvent to adjust the solid content concentration to 65%, and then mixed with a planetary mixer for 60 minutes. After that, diisobutyl ketone was further added to adjust the solid content concentration to 60%, and then mixed with a planetary mixer to prepare a slurry composition for the negative electrode composite layer.
[0094] <Preparation of Slurry Composition for Solid Electrolyte Layer> In a glove box under an argon gas atmosphere (water concentration 0.6 mass ppm, oxygen concentration 1.8 mass ppm), 100 parts of sulfide glass (Li2S / P2S5=70mol% / 30mol%, number average particle diameter: 0.9μm) consisting of Li2S and P2S5 as solid electrolyte particles was mixed with 2 parts (solid content equivalent) of the binder composition obtained as described above, and further, diisobutyl ketone was added as an organic solvent to adjust the solid content concentration to 60 mass%, and then mixed with a planetary mixer for 60 minutes. Thereafter, diisobutyl ketone was further added to adjust the solid content concentration to 45%, and then mixed with a planetary mixer to prepare a slurry composition for a solid electrolyte layer. Various measurements were performed using the obtained slurry composition for a solid electrolyte layer. The results are shown in Table 1.
[0095] <Manufacturing of all-solid-state secondary batteries> The above-mentioned slurry composition for the positive electrode composite layer was applied to the surface of a current collector (aluminum foil, thickness: 20 μm) and dried (at 120° C. for 60 minutes) to form a positive electrode composite layer (solid electrolyte-containing layer) having a thickness of 50 μm, thereby obtaining a positive electrode. The peel strength and pressability of the positive electrode were measured using this positive electrode. The results are shown in Table 1. In addition, the above-mentioned slurry composition for the negative electrode composite layer was applied to the surface of another current collector (copper foil, thickness: 15 μm) and dried (temperature 120° C., 60 minutes) to form a negative electrode composite layer (solid electrolyte-containing layer) with a thickness of 60 μm, thereby obtaining a negative electrode. Next, the solid electrolyte layer slurry composition was applied to an imide film (thickness: 25 μm) and dried (at 120° C. for 60 minutes) to form a solid electrolyte layer (solid electrolyte-containing layer) having a thickness of 150 μm. The positive electrode mixture layer and the solid electrolyte layer were bonded together so that they were in contact with each other, and a pressing process was performed so that a pressure (pressing pressure) of 400 MPa was applied, and the solid electrolyte layer was transferred from the imide film to the positive electrode mixture layer, thereby obtaining a positive electrode with a solid electrolyte layer. The positive electrode with the solid electrolyte layer and the negative electrode were attached together so that the solid electrolyte layer of the positive electrode with the solid electrolyte layer and the negative electrode composite layer of the negative electrode were in contact with each other, and a press treatment was performed so that a pressure (press pressure) of 400 MPa was applied to the solid electrolyte layer (solid electrolyte-containing layer) of the positive electrode with the solid electrolyte layer, to obtain an all-solid-state secondary battery. The thickness of the solid electrolyte layer of the all-solid-state secondary battery after pressing was 120 μm. The cell resistance and cell characteristics (cycle characteristics) were measured using this all-solid-state secondary battery. The results are shown in Table 1.
[0096] Example 2 In preparing the binder composition, 25 parts of phenoxyethyl acrylate as an ether group-containing monomer was used instead of styrene as an aromatic monomer as a monomer, but the binder composition, the slurry composition for the positive electrode mixture layer, the slurry composition for the negative electrode mixture layer, the slurry composition for the solid electrolyte layer, and the all-solid secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 1.
[0097] (Examples 3 and 4) In preparing the binder composition, the content of the element belonging to Group 13 and / or Group 14 of the periodic table relative to the polymer contained in the binder composition was adjusted to 4300 mass ppm (Example 3) and 12 mass ppm (Example 4). Except for this, the binder composition, the slurry composition for the positive electrode mixture layer, the slurry composition for the negative electrode mixture layer, the slurry composition for the solid electrolyte layer, and the all-solid secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 1.
[0098] Example 5 In preparing the binder composition, a binder composition, a slurry composition for a positive electrode mixture layer, a slurry composition for a negative electrode mixture layer, a slurry composition for a solid electrolyte layer, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, except that a second synthetic zeolite (manufactured by Shin-Etsu Chemical Industry Co., Ltd., product name "Molecular Sieves 13X", shape: powder, particle size: 325 mesh, solubility in water at a temperature of 25°C: 0.1%) was used instead of the first synthetic zeolite as a compound containing an element belonging to Group 13 and / or Group 14 of the periodic table, and various evaluations were performed. The results are shown in Table 1.
[0099] Example 6 In preparing the binder composition, a third synthetic zeolite (manufactured by Shin-Etsu Chemical Industry Co., Ltd., product name "Molecular Sieves 3A", shape: powder, particle size: 325 mesh, solubility in water at 25°C: 0.2%) was used instead of the first synthetic zeolite as a compound containing an element belonging to Group 13 and / or Group 14 of the periodic table. Except for this, a binder composition, a slurry composition for a positive electrode mixture layer, a slurry composition for a negative electrode mixture layer, a slurry composition for a solid electrolyte layer, and an all-solid secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 1.
[0100] Example 7 In preparing the binder composition, a fourth synthetic zeolite (manufactured by Zeochem, product name "ZEOflair110", shape: powder, particle size: 325 mesh, solubility in water at 25°C: 0.1%) was used instead of the first synthetic zeolite as a compound containing an element belonging to Group 13 and / or Group 14 of the periodic table. Except for this, a binder composition, a slurry composition for a positive electrode mixture layer, a slurry composition for a negative electrode mixture layer, a slurry composition for a solid electrolyte layer, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 1.
[0101] Example 8 In preparing the binder composition, a binder composition, a slurry composition for a positive electrode mixture layer, a slurry composition for a negative electrode mixture layer, a slurry composition for a solid electrolyte layer, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, except that silica gel (manufactured by Toyoda Chemical Industry Co., Ltd., product name "Silica Gel Type A", solubility in water at 25°C 0.3%) was used instead of the first synthetic zeolite as the compound containing an element belonging to Group 13 and / or Group 14 of the periodic table, and various evaluations were performed. The results are shown in Table 2.
[0102] Example 9 In preparing the binder composition, 71 parts of n-butyl acrylate was used as the carbonyl group-containing monomer, 3 parts of methacrylic acid as the carboxyl group-containing monomer, 6 parts of acrylonitrile as the vinyl cyanide monomer, and 20 parts of styrene as the aromatic monomer. Except for this, the binder composition, the slurry composition for the positive electrode mixture layer, the slurry composition for the negative electrode mixture layer, the slurry composition for the solid electrolyte layer, and the all-solid secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 2.
[0103] Example 10 In preparing the binder composition, except that 2-hydroxyethyl acrylate was used as a hydroxyl group-containing monomer instead of the carboxyl group-containing monomer, the binder composition, the slurry composition for the positive electrode mixture layer, the slurry composition for the negative electrode mixture layer, the slurry composition for the solid electrolyte layer, and the all-solid secondary battery were prepared in the same manner as in Example 9, and various evaluations were performed. The results are shown in Table 2.
[0104] (Examples 11, 12, 16, and 17) In preparing the binder composition, except that butyl butyrate (Example 11), mesitylene (Example 12), xylene (Example 16), and isobutyl isobutyrate (Example 17) were used as the organic solvent instead of diisobutyl ketone, the binder composition, the slurry composition for the positive electrode composite layer, the slurry composition for the negative electrode composite layer, the slurry composition for the solid electrolyte layer, and the all-solid secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Tables 2 and 3.
[0105] Example 13 Except for using the binder composition prepared as follows, a positive electrode mixture layer slurry composition, a negative electrode mixture layer slurry composition, a solid electrolyte layer slurry composition, and an all-solid secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 2.
[0106] <Preparation of Binder Composition> A reactor was charged with 2 parts of potassium oleate as an emulsifier, 0.1 parts of potassium phosphate as a stabilizer, and 150 parts of water, and further added with 35 parts of n-butyl acrylate as a carbonyl group-containing monomer, 19 parts of acrylonitrile as a vinyl cyanide monomer, 31 parts of 1,3-butadiene as a conjugated diene monomer, 15 parts of styrene as an aromatic monomer, and 0.31 parts of t-dodecyl mercaptan as a molecular weight regulator, and emulsion polymerization was initiated at a temperature of 10° C. in the presence of 0.015 parts of ferrous sulfate as an activator and 0.05 parts of paramenthane hydroperoxide as a polymerization initiator. When the polymerization conversion rate reached 85%, 0.2 parts of hydroxylamine sulfate per 100 parts of monomer was added to terminate the polymerization. Following termination of the polymerization, the mixture was heated and subjected to steam distillation under reduced pressure at a temperature of 70° C. to recover unreacted monomers, after which 2 parts of alkylated phenol were added as an antioxidant to obtain a polymer (copolymer latex).
[0107] <<Hydrogenation reaction>> 400mL of the resulting aqueous dispersion of the polymer (total solid content: 48g) was placed in a 1-liter autoclave equipped with a stirrer, and nitrogen gas was passed through for 10 minutes to remove dissolved oxygen in the polymer solution. Then, 50mg of palladium acetate was dissolved in 180mL of water containing 4 times the molar amount of nitric acid relative to Pd as a hydrogenation catalyst and added. After replacing the system twice with hydrogen gas, the contents of the autoclave were heated to a temperature of 50°C while pressurizing with hydrogen gas up to a pressure of 3MPa, and hydrogenation reaction was carried out for 6 hours. The contents were returned to room temperature, the inside of the system was filled with nitrogen, and the contents were then concentrated using an evaporator until the solid content reached 40%, to obtain a polymer (hydrogenated nitrile rubber). 100 g of the obtained polymer (hydrogenated nitrile rubber) was coagulated with 1 L of methanol, and then vacuum dried at 60° C. for 12 hours. 1 The polymer was analyzed by H-NMR. Based on the analytical values obtained, the content (%) of each monomer unit and structural unit contained in the polymer was calculated. The results are shown in Table 2. Next, an appropriate amount of diisobutyl ketone was added to the obtained aqueous dispersion of the polymer to obtain a mixture, which was then distilled under reduced pressure at a temperature of 80° C. to remove water and excess diisobutyl ketone from the mixture to obtain a binder precursor composition (solid content concentration: 8%). Furthermore, 5 parts of a first synthetic zeolite (manufactured by Shin-Etsu Chemical Industry Co., Ltd., product name "Molecular Sieves 4A, shape: powder, particle size: 325 mesh", solubility in water at a temperature of 25°C: less than 0.1%) was added to the binder precursor composition as a compound containing an element belonging to Group 13 and / or Group 14 of the periodic table, and after 24 hours, the mixture was filtered through a 10 μm filter to obtain a binder composition.
[0108] Example 14 A slurry composition for a positive electrode mixture layer, a slurry composition for a negative electrode mixture layer, a slurry composition for a solid electrolyte layer, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, except that two types of polymers, polymer A and polymer B (the mass ratio of polymer A to polymer B was 1:1), were used as the polymer, and various evaluations were performed. The results are shown in Table 3. Polymer A and polymer B were prepared as follows.
[0109] <Preparation of Dispersion of Polymer A in Diisobutyl Ketone> 100 parts of ion-exchanged water was added to a 1 L flask equipped with a stirrer and a septum, the gas phase was replaced with nitrogen gas, and the temperature was raised to 70°C. After that, a solution in which 0.5 parts of ammonium persulfate (APS) as a polymerization initiator was dissolved in 20.0 parts of ion-exchanged water was added. Meanwhile, in another vessel, 40 parts of ion-exchanged water, 1.0 part of sodium dodecylbenzenesulfonate as an emulsifier, 50 parts of n-butyl acrylate and 20 parts of ethyl acrylate as carbonyl group-containing monomers, 10 parts of acrylonitrile as a vinyl cyanide monomer, and 20 parts of styrene as an aromatic vinyl monomer were mixed to obtain a monomer composition. The obtained monomer composition was continuously added to the above-mentioned 1 L flask with a septum over a period of 2 hours to carry out polymerization. During the addition of the monomer composition, the reaction temperature was set to 70° C. After the addition of the monomer composition, the mixture was stirred at a temperature of 80° C. for 3 hours, and then the polymerization was terminated. Then, an appropriate amount of diisobutyl ketone as an organic solvent was added to the obtained aqueous dispersion of polymer A to obtain a mixture. Thereafter, water and excess diisobutyl ketone were removed from the mixture by vacuum distillation at a temperature of 80° C., to obtain a diisobutyl ketone dispersion of polymer A (solid content: 8%).
[0110] <Preparation of Dispersion of Polymer B in Diisobutyl Ketone> 100 parts of ion-exchanged water was added to a 1 L flask equipped with a stirrer and a septum, the gas phase was replaced with nitrogen gas, and the temperature was raised to 70°C. After that, a solution in which 0.5 parts of ammonium persulfate (APS) as a polymerization initiator was dissolved in 20.0 parts of ion-exchanged water was added. Meanwhile, in another container, 40 parts of ion-exchanged water, 1.0 part of sodium dodecylbenzenesulfonate as an emulsifier, 54.5 parts of n-butyl acrylate and 25 parts of ethyl acrylate as carbonyl group-containing monomers, 10 parts of acrylonitrile as a vinyl cyanide monomer, 10 parts of styrene as an aromatic monomer, and 0.5 parts of allyl methacrylate as other monomers were mixed to obtain a monomer composition. The obtained monomer composition was continuously added to the above-mentioned 1 L flask with a septum over a period of 2 hours to carry out polymerization. During the addition of the monomer composition, the reaction temperature was set to 70° C. After the addition of the monomer composition, the mixture was stirred at a temperature of 80° C. for 3 hours, and then the polymerization was terminated. Then, an appropriate amount of diisobutyl ketone as an organic solvent was added to the obtained aqueous dispersion of polymer B to obtain a mixture. Thereafter, water and excess diisobutyl ketone were removed from the mixture by vacuum distillation at a temperature of 80° C., to obtain a diisobutyl ketone dispersion of polymer B (solid content: 8%).
[0111] <Preparation of Binder Composition Containing Polymer A and Polymer B> The diisobutyl ketone dispersion of polymer A and the diisobutyl ketone solution of polymer B obtained as described above were mixed in a ratio (solid content equivalent) of polymer A:polymer B=1:1 to prepare a binder composition.
[0112] Example 15 In preparing the binder composition, 52 parts of n-butyl acrylate and 42 parts of ethyl acrylate were used as the carbonyl group-containing monomer, 3 parts of methacrylic acid as the carboxyl group-containing monomer, and 3 parts of 2-hydroxyethyl acrylate as the hydroxyl group-containing monomer, but the binder composition, the slurry composition for the positive electrode mixture layer, the slurry composition for the negative electrode mixture layer, the slurry composition for the solid electrolyte layer, and the all-solid secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 3.
[0113] (Example 18) In preparing the binder composition, 65 parts of n-butyl acrylate and 25 parts of ethyl acrylate were used as the carbonyl group-containing monomer, and 10 parts of acrylonitrile as the vinyl cyanide monomer, but the binder composition, the slurry composition for the positive electrode mixture layer, the slurry composition for the negative electrode mixture layer, the slurry composition for the solid electrolyte layer, and the all-solid secondary battery were prepared in the same manner as in Example 16, and various evaluations were performed. The results are shown in Table 3.
[0114] Comparative Example 1 In preparing the binder composition, except that no compound containing an element belonging to Group 13 and / or Group 14 of the periodic table was used, the binder composition, the slurry composition for the positive electrode mixture layer, the slurry composition for the negative electrode mixture layer, the slurry composition for the solid electrolyte layer, and the all-solid secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 4.
[0115] Comparative Example 2 In preparing the binder composition, the content of elements belonging to Group 13 and / or Group 14 of the periodic table in the binder composition was adjusted to 10,000 mass ppm, but the binder composition, the slurry composition for the positive electrode mixture layer, the slurry composition for the negative electrode mixture layer, the slurry composition for the solid electrolyte layer, and the all-solid secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 4.
[0116] Comparative Example 3 In preparing the polymer, sodium hydroxide was used to adjust the binder composition to contain Na instead of the elements belonging to Group 13 and / or Group 14 of the periodic table, but the binder composition, the slurry composition for the positive electrode mixture layer, the slurry composition for the negative electrode mixture layer, the slurry composition for the solid electrolyte layer, and the all-solid secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 4.
[0117] Comparative Example 4 In preparing the polymer, sodium hydroxide and calcium hydroxide were used to adjust the binder composition to contain Na and Ca instead of the elements belonging to Group 13 and / or Group 14 of the periodic table, but the binder composition, the slurry composition for the positive electrode mixture layer, the slurry composition for the negative electrode mixture layer, the slurry composition for the solid electrolyte layer, and the all-solid secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 4.
[0118] In addition, in Tables 1 to 3 shown below, "BA" indicates n-butyl acrylate units; "PEA" indicates a phenoxyethyl acrylate unit; "EA" indicates an ethyl acrylate unit; "MAA" indicates a methacrylic acid unit, "B-HEA" indicates a 2-hydroxyethyl acrylate unit, "AN" indicates an acrylonitrile unit, "ST" indicates a styrene unit, "H-BD" indicates a 1,3-butadiene hydride unit; "AMA" indicates an allyl methacrylate unit; "DIK" stands for diisobutyl ketone, "HB" stands for butyl butyrate; "MES" refers to mesitylene.
[0119] [Table 1]
[0120] [Table 2]
[0121] [Table 3]
[0122] [Table 4]
[0123] From Tables 1 to 3, it can be seen that by using binder compositions (Examples 1 to 18) containing a polymer, an organic solvent, and a compound having a solubility in water at a temperature of 25° C. of 10 mass % or less and containing an element belonging to Group 13 and / or Group 14 of the periodic table (excluding carbon and germanium), in which the content of the element in the binder composition is 5 ppm by mass or more and 5,000 ppm by mass or less with respect to the polymer, an all-solid-state secondary battery having excellent water resistance and excellent battery characteristics can be manufactured. In contrast, when a binder composition not containing the above compound (Comparative Example 1), a binder composition in which the content of the element belonging to Group 13 and / or Group 14 of the periodic table relative to the polymer in the binder composition is outside the above range (Comparative Example 2), or a binder composition not containing an element belonging to Group 13 and / or Group 14 of the periodic table (Comparative Examples 3 and 4) is used, it is found that the water resistance and battery characteristics of the obtained all-solid-state secondary batteries are inferior to those of the all-solid-state secondary batteries obtained in each Example. [Industrial Applicability]
[0124] According to the present invention, it is possible to provide a binder composition for a secondary battery that can improve the water resistance of the secondary battery and enable the secondary battery to exhibit excellent battery characteristics. Moreover, according to the present invention, it is possible to provide a slurry composition for a secondary battery that can improve the water resistance of the secondary battery and enable the secondary battery to exhibit excellent battery characteristics. Furthermore, according to the present invention, it is possible to provide a solid electrolyte-containing layer having excellent water resistance, and an all-solid-state secondary battery having excellent battery characteristics, and a method for producing the same.
Claims
1. A polymer; An organic solvent; A binder composition for a secondary battery comprising: the compound has a solubility of 10 mass % or less in water at a temperature of 25° C., and contains an element belonging to Group 13 and / or Group 14 of the Periodic Table (excluding carbon and germanium); the compound is at least one selected from the group consisting of zeolite, silica gel, and polydimethylsiloxane; a content of the element in the binder composition for a secondary battery being 5 ppm by mass or more and 5000 ppm by mass or less with respect to the polymer;
2. 2. The binder composition for a secondary battery according to claim 1, wherein the polymer has at least one functional group selected from the group consisting of a carbonyl group, an ether group, a carboxy group, and a hydroxy group.
3. 3. The binder composition for a secondary battery according to claim 1, wherein the polymer contains vinyl cyanide monomer units in a ratio of 2% by mass or more and 35% by mass or less.
4. The binder composition for a secondary battery according to any one of claims 1 to 3, wherein the polymer contains aromatic monomer units in a ratio of 5% by mass to 40% by mass.
5. The binder composition for secondary batteries according to any one of claims 1 to 4, wherein the polymer contains conjugated diene monomer units and / or alkylene structural units in a ratio of 20% by mass or more and 60% by mass or less.
6. A slurry composition for a secondary battery, comprising the binder composition for a secondary battery according to any one of claims 1 to 5.
7. The slurry composition for a secondary battery according to claim 6 , comprising a solid electrolyte.
8. A solid electrolyte-containing layer formed using the slurry composition for a secondary battery according to claim 7.
9. An all-solid-state secondary battery comprising the solid electrolyte-containing layer according to claim 8.
10. A method for producing an all-solid-state secondary battery, comprising the step of pressing the solid electrolyte-containing layer according to claim 8 at a pressure of less than 300 MPa.
Citation Information
Patent Citations
Detection of defect of extra-thin organic film
JP1988090744A
All-solid type secondary battery and method for manufacturing all-solid type secondary battery
JP2015103451A
All-solid type secondary battery, battery electrode sheet, method for manufacturing battery electrode sheet, solid electrolytic composition, method for manufacturing solid electrolytic composition, and method for manufacturing all-solid type secondary battery
JP2016033917A
Positive electrode active material for lithium ion battery, positive electrode for lithium ion battery, and lithium ion battery
JP2016162602A
Negative electrode for all-solid battery
JP2017054720A